Thomas Edison : PHYSICIST AND INVENTOR - Boone, Mary, 1963-; Butzer, Anna; Nuytten, Bobbie (North Mankato, Minnesota : CAPSTONE PRESS, 2018)
"Thomas Edison wasn't just an inventor. He was also a physicist and businessman. Young readers will discover how he became a great scientist whose inventions made a better life for most everyone"--Provided by publisher.
Includes index.
Bibliography : page 23
Interest age level: Ages 6-9.
Keywords: Edison, Thomas A. (Thomas Alva), -- Juvenile literature -- 1847-1931; Inventors -- Juvenile literature -- Biography -- United States; Scientists -- Juvenile literature -- Biography -- United States